A snapshot algorithm for distributed mobile systems - Sato, Y.; Inoue, M.; Masuzawa, T.; Fujiwara, H. (Proceedings of the 16th International Conference on Distributed Computing Systems, 1996)
This paper considers distributed algorithms for distributed mobile systems. Many distributed algorithms have been designed for distributed systems consisting of static computers only. But most of them cannot be directly applied to mobile systems. This paper proposes a model of mobile systems. Management of movements of mobile hosts is abstracted in our model to simplify design of algorithms for mobile systems. This paper also defines the snapshot problem, one of the fundamental problems, on the model. The problem requires to find a strongly consistent configuration in which topological consistency is satisfied in addition to causal consistency. Furthermore, this paper presents a snapshot algorithm for mobile systems.